2023
DOI: 10.3892/or.2023.8531
|View full text |Cite
|
Sign up to set email alerts
|

METTL3/YTHDF2 m6A axis promotes the malignant progression of bladder cancer by epigenetically suppressing RRAS

Abstract: The present study aimed to explore the potential roles of the methyltransferase-like 3 (METTL3)-mediated methylation of RAS related (RRAS) mRNA in the tumorigenesis and development of bladder cancer (BCa). For this purpose, the relative expression levels of METTL3 in BCa specimens and cell lines were measured using reverse transcription-quantitative PCR (RT-qPCR) and western blot analysis. The association between the METTL3 expression level and the clinical characteristics of patients with BCa was analyzed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Recent evidence showed that METTL3 promotes cholangiocarcinoma progression by YTHDF2-mediated IFIT2 mRNA degradation [ 49 ]. METTL3 facilitates bladder cancer growth and metastasis by suppressing RRAS expression in a YTHDF2‑dependent manner [ 50 ]. To illuminate if YTHDF2 recognized the mRNA of Dkk3 and Sostdc1 and modulated the mRNA decay, RIP-PCR and RNA stability assay were performed.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence showed that METTL3 promotes cholangiocarcinoma progression by YTHDF2-mediated IFIT2 mRNA degradation [ 49 ]. METTL3 facilitates bladder cancer growth and metastasis by suppressing RRAS expression in a YTHDF2‑dependent manner [ 50 ]. To illuminate if YTHDF2 recognized the mRNA of Dkk3 and Sostdc1 and modulated the mRNA decay, RIP-PCR and RNA stability assay were performed.…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to develop cancer therapies on the basis of gene expression data have been made for various types of carcinomas. For example, studies based on gene expression data have been conducted in endometrial cancer [ 103 ], lung adenocarcinoma [ 104 ], and bladder cancer [ 105 ]. Regarding breast cancer, as we have introduced here, the search for repurposing drugs on the basis of gene expression data is underway.…”
Section: Discussionmentioning
confidence: 99%
“…About YTHDF2, the METTL3/YTHDF2 m 6 A axis promotes tumorigenesis in bladder cancer by mediating degradation of RRAS [ 235 ], SETD7, and KLF4 [ 236 ]. Also, METTL3 depletion suppressed metastasis [ 236 ].…”
Section: Molecular Alterations In Cancer Metastasismentioning
confidence: 99%